THE IMPLEMENTATION OF THE PROBLEM-BASED LEARNING MODEL BASED ON TORAJA CULTURE IN MATHEMATICS LEARNING: PENERAPAN MODEL PROBLEM-BASED LEARNING BERBASIS BUDAYA TORAJA DALAM PEMBELAJARAN MATEMATIKA - Lembang, Suri Toding; Arsyad, Nurdin; Bernard (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
This research aims to implement Toraja cultural-based mathematics teaching tools to enhance the learning outcomes of students at SMPN 1 Makale Selatan. The objectives include assessing students' learning outcomes, their activities, and the teacher's capability in applying Toraja cultural-based mathematics teaching tools. The research method employed is quantitative research. Based on the findings, students' learning outcomes through problem-based learning (PBL) models infused with Toraja cultural elements are categorized as very high, with an average score of 86.17. This success is attributed to the cultural relevance and emotional connection fostered by the PBL approach integrated with Toraja traditions. The inclusive learning environment created through the recognition of cultural diversity further contributes to positive outcomes, confirming the effectiveness of the Toraja culture-based PBL model in promoting active student involvement in the learning experience. The integration of Toraja cultural elements into the PBL model significantly contributes to the remarkable success in achieving a high average score of 86.17 in students' learning outcomes. This achievement is found due to the contextual relevance of Toraja cultural values, increased emotional engagement, and the development of critical thinking skills within a broader cultural context. The use of Toraja culture not only enhances memory retention but also empowers students to actively participate in a learning environment that celebrates cultural diversity. The exceptional learning outcomes affirm the efficacy of integrating PBL with Toraja cultural elements, providing students with a profound and meaningful educational experience.